An Analysis of the Effectiveness of the Islamic Legal Framework of Matrimonial Incorporeal Darar (Mid) and the Practical Challenges in Obtaining Judicial Remedies in Kano State - Umar Shu'aibu Gokaru; Aisha Ali Tijjani (QURU’: Journal of Family Law and Culture, 2026)
Matrimonial incorporeal injury (MID) refers to non-physical harms or wrongs committed by a husband against his wife, such as verbal abuse, cruelty, lack of maintenance, sexual deprivation, abandonment, and controlling behavior. It encompasses all forms of damage, harm, or loss suffered by the wife and inflicted by the husband. In other words, MID includes all factors that negatively affect the rights of the wife and hinder her enjoyment of the marriage contract in any way. The major problem addressed in this study is the inability of litigants to provide sufficient evidence to prove this type of injury, as it usually occurs in private. Consequently, judges often overlook the injury and issue inappropriate judicial remedies, particularly to women, which in turn causes further harm. The main aim of the paper is to highlight the judicial shortcomings of Shari’a court judges when handling such cases and to explore ways of enhancing the effectiveness of the Islamic legal framework on MID. It also seeks to address the practical challenges in obtaining judicial remedies by using qualitative measures to collect data, given that an empirical approach was predominantly adopted. A doctrinal method was also partially used to analyze tertiary sources in order to demonstrate the occurrence of the phenomenon globally. One of the findings of the study is that this type of injury is frequently ignored by the courts, and compensation is rarely awarded. Major challenges include the difficulty of evidential procedures, the lack of awareness of women’s rights among both genders, and judges’ inadequate appreciation of the concept of MID. This situation enables parties to continue committing such wrongs without consequences. The study therefore recommends, among other measures, that religious leaders and preachers intensify public awareness on women’s matrimonial rights, and that judges develop improved procedures to help litigants sustain their claims by thoroughly exploring principles of Islamic law and exercising proper judicial activism to extract evidence.